Psychometric Validation and Measurement Invariance of the Flourishing Scale (FS) in the Algerian Context - Mohammed Mansouri (Measurement Instruments for the Social Sciences)
This study aims to validate the psychometric properties of the Flourishing Scale (FS) within the Algerian context, contributing to the understanding of psychological well-being in non-Western settings. Flourishing reflects an individual’s perception of leading a fulfilling and meaningful life, with optimal functioning across social, emotional, and psychological domains. Using a sample of 365 university students, the study evaluated the FS alongside the Satisfaction with Life Scale. EFA and CFA were conducted to examine the FS structure, along with internal consistency and validity assessments. The results demonstrated strong psychometric properties, confirming the scale’s unidimensionality, high internal consistency, and validity as a measure of flourishing in Algeria. Measurement invariance analysis further confirmed that the FS retains its psychometric robustness across gender and age groups, reinforcing its applicability in diverse populations. Correlations with SWLS further supported its construct validity. The findings support the use of the FS in Algerian settings to assess psychological well-being. Future research should explore its applicability across diverse demographic groups and investigate its relationships with other constructs, such as resilience and work-life balance.